Analisis Pengukuran Kinerja Instansi Pemerintahan Kabupaten Ngawi - Saputra, Aditya Eka (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This study focuses on measuring the performance of the Ngawi Regency in the Regional Medium-Term Development Plan (RPJMD) for 2016-2021. The author uses a measuring instrument value for money as a measure of the performance of regional apparatus. The author divides the discussion into 2 focuses, namely efforts to reduce poverty and efforts to improve the regional economy. In the poverty reduction sector, there are programs from the social service, while in improving the regional economy there are 8 sectors which include Food, Community Empowerment, MSMEs, Investment, tourism, agriculture, trade and industry. There is a grouping of these sectors into 3 sections of regional development which include Compulsory Non-Basic Services and Options. In the Non-Basic Service Compulsory group, it includes the Food sector, Community and Village Empowerment, MSMEs, Investment. Meanwhile, tourism, industry, and trade are the sectors of choice. The results of this study indicate that the performance in reducing poverty and increasing the economy gets the predicate of being economical, effective and efficient.